2016
DOI: 10.1002/pro.3031
|View full text |Cite
|
Sign up to set email alerts
|

Interaction mode between catalytic and regulatory subunits in glucosidase II involved in ER glycoprotein quality control

Abstract: The glycoside hydrolase family 31 (GH31) α-glucosidases play vital roles in catabolic and regulated degradation, including the α-subunit of glucosidase II (GIIα), which catalyzes trimming of the terminal glucose residues of N-glycan in glycoprotein processing coupled with quality control in the endoplasmic reticulum (ER). Among the known GH31 enzymes, only GIIα functions with its binding partner, regulatory β-subunit (GIIβ), which harbors a lectin domain for substrate recognition. Although the structural data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…PRKCSH consists of multiple domains, including a signal sequence for translocation across the ER membrane, an N-terminal GIIα-binding (G2B) domain, a putative coiled-coil segment, a glutamic acid and proline-rich (E/P) segment, and a C-terminal mannose 6-phosphate receptor homology (MRH) domain followed by an HDEL signal sequence for ER retention 27,28 . ER-translocation of PRKCSH is required for the expression and retention of GIIα in the ER lumen and maintaining optimal GII activity 29 . Genetic loss of PRKCSH is involved in autosomal dominant polycystic liver disease (ADPLD) 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…PRKCSH consists of multiple domains, including a signal sequence for translocation across the ER membrane, an N-terminal GIIα-binding (G2B) domain, a putative coiled-coil segment, a glutamic acid and proline-rich (E/P) segment, and a C-terminal mannose 6-phosphate receptor homology (MRH) domain followed by an HDEL signal sequence for ER retention 27,28 . ER-translocation of PRKCSH is required for the expression and retention of GIIα in the ER lumen and maintaining optimal GII activity 29 . Genetic loss of PRKCSH is involved in autosomal dominant polycystic liver disease (ADPLD) 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we found that residues in the distal C‐terminal region of GIIα intensively suffer from positive selection. GIIα is the only GH31 enzyme that can form a heterodimeric structure through its distal C‐terminal domain (Satoh, Toshimori, Noda, et al., ). Our finding implies that positive selection in the distal C‐terminal domain probably affects the heterodimeric structure of GIIα and folding conformation of the enzymic complexes.…”
Section: Discussionmentioning
confidence: 99%
“…GIIb can be recruited to modulate the catalytic activity and folding of GIIa and stabilizing the GII complex in vivo. Moreover, GIIb can recognize and bind cooperative substrates through its MRH domain to ensure the efficient glucose trimming of N-glycans (Deprez, Gautschi, & Helenius, 2005;Satoh, Toshimori, Noda, Uchiyama, & Kato, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…MOGS (also known as glucosidase I) is expressed in the endoplasmic reticulum and is involved in trimming N-glycans; it was the first enzyme to be identified in the pathway for processing N-linked oligosaccharides [ 30 ]. GII alpha belongs to glycoside hydrolase family 31 (GH31), which has similar functions as MOGS and is involved in trimming N-glycans [ 31 ]. As a recognized inhibitor of α-glucosidase, DNJ also inhibits MOGS and GII alpha activities [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%